Screening the Vitis genus for tolerance to boron with and without salinity. (30th August 2013) - Pech, J.M.; Stevens, R.M.; Grigson, G.J.; Cox, J.W.; Schrale, G.
Abstract: Background and Aims: Alternative sources of irrigation water can contain excess boron. Twenty‐six grapevine genotypes were assessed for their tolerance to excess boron under non‐saline and saline conditions. Methods and Results: Rootling vines received one of three irrigation treatments: Control (B 0.2 mM), Boron (B 0.67 mM) or Boron+Salt [B 0.6 mM, electrical conductivity 4.0 dS/m]. In the Boron treatment, shoot growth ranged from 88 to 14% of that in the Control, and in the Boron+Salt from 58 to 10% of that in the Control. Within genotype comparison showed that the growth of shoots in the Boron and Boron+Salt treatments was equivalent in 24 genotypes. Genotype did not affect the leaf B concentration in the Boron treatment. The addition of salinity did not affect the leaf B concentration in 25 genotypes. In 14 genotypes, the leaf Na + concentration in the Boron treatment was more than double that in the Control. In the Boron and Boron+Salt treatments, shoot growth was not correlated with B concentration in the leaf, and in the Boron+Salt treatment, it was not correlated with Cl − and Na + concentration in the leaf. Boron and Boron+Salt treatments reduced the leaf photosynthetic rate and the effective quantum yield of photosystem II (ΦPSII ). Conclusions: There was a large genotypic variation in the tolerance of growth to excess boron. It could not be attributed to the variation in leaf B concentration. Significance of the Study: The shoot growth in 1613 Couderc and Vitis acerifolia under excess boron was equivalent to that in the Control treatment, which indicates that the use of these two genotypes as rootstocks may produce vines with an improved tolerance to excess boron.